Health outcomes and healthcare delivery systems for pregnant and postpartum individuals in immigration detention settings: A scoping review protocol - Elizabeth Kravitz; Daniel Delmonaco; Chelsea A. DeBolt (PLoS ONE, 2026)
Pregnant and postpartum individuals in immigration detention may experience barriers to accessing timely and appropriate perinatal care. The existing literature remains fragmented across global settings. This scoping review protocol aims to map the extent, range, and nature of evidence on health outcomes and healthcare delivery systems for pregnant and postpartum individuals in immigration detention. Following the Arksey and O’Malley framework and PRISMA-ScR guidelines, peer-reviewed studies and relevant grey literature will be included without language restrictions, after January 2000. Two reviewers will independently screen sources, and a third will perform full text review and extract data. Findings will be synthesized descriptively and thematically.